MACROZOOBENTHOS COMMUNITY STRUCTURE IN INTERTIDAL ZONE OF SAMBUNGO VILLAGE PESISIR SELATAN REGENCY OF WEST SUMATERA PROVINCE - Anggara, Bob; Tanjung, Afrizal; Nasution, Syafruddin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2021)
This research was conducted in the village of Sambungo, Silaut District, Pesisir Selatan Regency, West Sumatra Province in August 2020. The purpose of this study was to determine the structure of the macrozoobenthos community which includes: type, density, diversity, uniformity, dominance and distribution patterns. Sampling was done randomly at 3 stations, each station consists of 3 transects and each transect consists of 3 plots, namely in the upper middle and lower in the intertidal zone. The results of the study found 5 classes of macrozoobenthos with 9 species. The abundance values ​​obtained ranged from 3.33 - 5.11 ind/m2. The diversity index value ranges from 1.18-1.54 which is classified as moderate, while the dominance index value ranges from 0.39-0.52, namely there was no species that dominate, the uniformity index value ranges from 0.03-0.06 which is not balanced and the value of the distribution pattern ranges from 2.81 to 3.76 with the pattern of distribution in groups.